The Effect of Using Educational Drama on Kindergarten Children's Acquisition of Mathematical and Scientific Concepts in Jordan - Mohammad A. Al-Khateeb (Sultan Qaboos University, 2018)
The study aimed to examin the effect of using educational drama on kindergarten children's acquisition of mathematical and scientific concepts. A quasi-experimental method with experimental and control groups was usedto achieve the objectives of the study. Various instruments were used, including a teacher's guide based on educational drama strategy and a scientific/mathematical concepts test. After validating these instruments, they were applied on a random sample of 50 kindergarten children during the first semester of school year 2016/2017. The study concluded that the experimental group outperformed control group on the scientific/mathematical concepts test. The findings also revealed that there were no significant statistical differences attributed to gender of the experimental group in the acquisition of such concepts.